We fell apart / E. Lockhart. - Lockhart, E. (We were liars novels., 2025)
The invitation arrives out of the blue. In it, Matilda discovers a father she's never met. Kingsley Cello is a visionary, a reclusive artist. And when he asks her to spend the summer at his seaside home, Hidden Beach, Matilda expects to find a part of herself she's never fully understood. Instead, she finds Meer, her long-lost, open-hearted brother; Brock, a former child star battling demons; and brooding, wild Tatum, who just wants her to leave their crumbling sanctuary. With Kingsley nowhere to be seen, Matilda must delve into the twisted heart of Hidden Beach to uncover the answers she's desperately craving. But secrets run thicker than blood, and blood runs like seawater. And everyone here is LYING.